Perubahan Globalisasi Teknologi Industri Menjadi Tantangan Guru PAI di Masa 4.0 - Adisel, Adisel; Prananosa, Ahmad Gawdy; Handayani, Puspa; Fauzi, Isman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the challenges of Islamic Religious Education teachers in facing changes in the era of globalization of the technology industry 4.0. The research method used is descriptive qualitative and refers to case studies. The results of the study indicate that the challenges faced by PAI teachers in the changing era of globalization of the technology industry 4.0, there are several challenges, one of which is that teachers are required to be digitally literate. Another challenge faced by PAI teachers is that teachers must be able to innovate their teaching methods in accordance with existing developments. Apart from teachers, other challenges come from students, where students' morale is eroded due to changes in the globalization of technology, and students' social actions towards their environment are also eroded, not only among students but also an indifferent attitude towards their responsibilities as students. In conclusion, as a PAI teacher, you must increase your understanding and knowledge in technology in order to implement this knowledge in the teaching process, especially in the era of globalization and changes in industrial technology in the 4.0 era as it is today. Keywords: Globalization 4.0, PAI, Teacher Challenges, Industrial Technology